2012
DOI: 10.1016/j.bbamcr.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin involvement in respiratory chain function and retinal ganglion cell integrity

Abstract: Neuroglobin is a member of the globin superfamily expressed in vertebrate brain and retina. The protein is thought to be involved in neuronal protection from hypoxia or oxidative stress and could represent a key element of Alzheimer disease pathogenesis. Our aim was to determine whether neuroglobin could be directly associated with mitochondrial metabolism and integrity. We identified three different forms of neuroglobin in the retina, varying in their apparent molecular masses; all forms are abundant in mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 53 publications
7
62
0
Order By: Relevance
“…This phenomenon of dimerization, resistant to heat denaturation and reduction, has been observed previously for Ngb in whole protein extracts from mouse brain and retinas [45][46][47][48]. Furthermore, it has been shown that three forms of apparent molecular masses (∼17, ∼19 and ∼21 kDa), specifically recognized by anti-Ngb antibodies, were identified in mitochondrial enriched fractions of mouse retina [49]. This pattern of three different molecular mass forms is similar to the one that is seen after expression of NGB in Sf9 insect cells (Fig.…”
Section: Expression Of Ngb Ch-iq-ab and Full Length Adgb In Sf9 Cellssupporting
confidence: 73%
See 1 more Smart Citation
“…This phenomenon of dimerization, resistant to heat denaturation and reduction, has been observed previously for Ngb in whole protein extracts from mouse brain and retinas [45][46][47][48]. Furthermore, it has been shown that three forms of apparent molecular masses (∼17, ∼19 and ∼21 kDa), specifically recognized by anti-Ngb antibodies, were identified in mitochondrial enriched fractions of mouse retina [49]. This pattern of three different molecular mass forms is similar to the one that is seen after expression of NGB in Sf9 insect cells (Fig.…”
Section: Expression Of Ngb Ch-iq-ab and Full Length Adgb In Sf9 Cellssupporting
confidence: 73%
“…3A). These forms might represent atypical migrations of stable protein conformations and it has been hypothesized that rupture/ formation of the intra molecular (CD7-B5) disulfide bond of NGB [50] can give rise to different apparent molecular mass forms [49]. Posttranslational modifications could also occur, such as covalent links of cofactors or phosphorylation.…”
Section: Expression Of Ngb Ch-iq-ab and Full Length Adgb In Sf9 Cellsmentioning
confidence: 99%
“…A number of studies have reported high levels of Ngb in the retina and adverse effects of Ngb knockdown on neuronal survival, leading the hypothesis that Ngb is important for retinal oxygen homeostasis and neuronal survival (7)(8)(9)(10)(11)(12)(13)(14)(30)(31)(32). Recently, Chan et al (13) found that transgenic overexpression of Ngb conferred protection against retinal ischemia via a decrease in oxidative stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chan et al (13) found that transgenic overexpression of Ngb conferred protection against retinal ischemia via a decrease in oxidative stress levels. Similarly, Lechauve et al (14) showed that siRNA knockdown of Ngb reduced mitochondrial activity, induced cell death and had an adverse effect on visual performance. In the present study, genome-wide transcriptional Expression was normalized to hypoxanthine phosphoribosyltransferase 1 (Htpr1) as the internal reference (n=9-10 in each group).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation